2023
DOI: 10.3390/land12071346
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Livelihood Capital Endowment on Household Poverty Alleviation: The Mediating Effect of Land Transfer

Abstract: (1) Background: Poverty eradication is the common goal and challenge of human development. Livelihood capital is the basis for poor families to escape poverty and is also the key to enhancing the ability for sustainable development. (2) Methods: Using data from the 2018 China Family Panel Studies (CFPS), this paper empirically examines the impact of livelihood capital on poverty alleviation. In addition, the mediating effect of land transfer is explored. (3) Results: The results show that human, physical, fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The primary goal of the TPA program was to uplift approximately 70 million people from poverty by 2020 [ 14 , 45 ]. Multiple studies have indicated the effectiveness of China’s TPA program in increasing the income of impoverished rural households [ 14 , 31 , 45 48 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The primary goal of the TPA program was to uplift approximately 70 million people from poverty by 2020 [ 14 , 45 ]. Multiple studies have indicated the effectiveness of China’s TPA program in increasing the income of impoverished rural households [ 14 , 31 , 45 48 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Farmers can cultivate crops on their land for personal consumption or sell the products for subsistence. Alternatively, they can transfer out the land and earn rental income to fulfill their basic needs [26][27][28]. In 2022, farmers possessed contracted land with about 0.1 hectares of arable land per capita and 0.52 hectares per household.…”
Section: Introductionmentioning
confidence: 99%